Spectroscopic evidences for the size dependent generation of pd species responsible for the low temperature CO oxidation activity on Pd-SBA-15 nanocatalyst - Soni, Yogita; Pradhan, Sumanta; Bamnia, Mahesh K.; Yadav, A. K.; Jha, S. N.; Bhattacharyya, D.; Khan, Tuhin Suvra; Haider, M. A.; Vinod, C. P. (Applied Catalysis B-Environmental, 2020)
A comprehensive size dependent CO oxidation activity has been demonstrated for Pd-SBA-15 catalysts with Pd NPs of varying sizes such as 1-2, 4-6 and 7-10 nm. Pd-SBA-15 catalyst with smallest sized NPs (Pd-S-N) has been synthesized by modified deposition precipitation method recently developed in our lab. Pd-S-N catalyst (reduced at 400 degrees C) demonstrated CO oxidation activity with lower light off temperature (50 degrees C), clearly one of the best reported for a Pd-silica system. A detailed XPS and in-situ DRIFTS analyses further supported by XAS and DFT calculations reveal the presence of easily decomposable highvalent Pd-oxide on co-ordinatively unsaturated Pd sites (Pdcus). Weak binding of CO on Pdcus sites in small Pd NPs leaving sites for oxygen activation is attributed to the low temperature activity of Pd-S-N for CO oxidation.
Keywords: CO oxidation; high-valent Pd species; Pd nanoparticles; SBA-15; under coordinated Pd atoms

Ultra-small Pd nanoparticles on SBA-15: an efficient catalyst for one-pot reductive alkylation of nitrobenzene with size-dependent activity - Soni, Yogita; Philip, Milda C.; Vinod, Chathakudath P. (Topics in Catalysis, 2025)
One-pot reductive alkylation of nitrobenzene with alcohol is an important organic synthesis reaction to form 2 degrees amines. In the present work, we have demonstrated that Pd/SBA-15 can be an effective catalytic system for this reaction. We have designed ultra-small Pd nanoparticles supported on SBA-15 for the synthesis of secondary amine, N-ethylaniline, through one-pot reductive alkylation of nitrobenzene with ethanol under ambient conditions. Ethanol functions both as the alkylating agent and the solvent in this process. The reaction is driven by the simultaneous hydrogenation of nitrobenzene to aniline, dehydrogenation of ethanol to aldehyde, and condensation of aniline and acetaldehyde to form N-ethylaniline. The size of the Pd nanoparticles plays a decisive role in the product selectivity. The undercoordinated sites present on ultra-small Pd NPs can facilitate ethanol dehydrogenation to acetaldehyde, thereby enhancing the selectivity towards N-ethylaniline compared to larger Pd nanoparticles. We have also studied the effect of different mesoporous supports such as SBA-15, MCM-41, and KIT-6 on the N-ethylaniline selectivity and found that SBA-15 was most selective. We have demonstrated that by carefully designing the catalyst such as controlling the Pd NPs size to obtain the maximum quantity of undercoordinated sites and choosing suitable support, the aliphatic alcohols can also be used for reductive alkylation of nitrobenzene in one-pot with optimum yields of N-alkylaniline.
Keywords: KIT-6; MCM-41; Modified deposition precipitation; nitrobenzene; Pd nanoparticles; Reductive alkylation; SBA-15; secondary amines; Undercoordinated Pd sites